The horse and his boy - Lewis, C. S. (Clive Staples) 1898-1963 (Lewis, C. S. 1898-1963. (Clive Staples) Chronicles of Narnia (HarperCollins (Firm)), 1982)
A boy and a talking horse share an adventurous and dangerous journey to Narnia to warn of invading barbarians.